Evaluation of potential probiotic bacteria for microalgae propagation and Artemia fransiscana (Kellog, 1906) bioencapsulation - Rosland, Nur Natasya Ain (2018)
The emergence of aquaculture industry is in need for non-antibiotic based disease control approach to minimize risk of antibiotic-resistance bacteria. Bacterial infections mainly caused by Vibrio spp. have caused mass mortalities to fish especially during larval stages. The potential of microalgae as future feedstocks in aquaculture sector has prompted to a new area of research in finding potential probiotics that can enhance algal biomass and at the same time, suppress fish larval pathogens. The current research was undertaken to discover new potential probiont strains isolated from microalgae and elucidate their interaction. The capability of the potential probionts in protecting Artemia from Vibrio spp. was also determined in this study. A total of 27 strains were successfully isolated from different species of fresh microalgae cultures (Amphora sp., Chaetoceros sp., Chlorella sp., Nannochlorum sp. and Spirulina sp.). All the isolated strains were screened for antibacterial activity against fish pathogens, Vibrio harveyi and Vibrio parahaemolyticus in in vitro study. Results of the agar well diffusion assay showed that 4 out of 27 strains were able to inhibit the growth of V. harveyi and V. parahaemolyticus. Strains labeled as A-1, A-2 and Cl-3 showed inhibition towards both pathogens tested while strain S-2 showed inhibition towards V. parahaemolyticus only. These four potential probionts were identified as Lysinibacillus fusiformis strain A-1 (isolated from Amphora sp.), Bacillus sp. strain A-2 (isolated from Amphora sp.), Lysinibacillus fusiformis strain Cl-3 (isolated from Chlorella sp.) and Bacillus pocheonensis strain S-2 (isolated from Spirulina sp.) using 16s rRNA molecular method. Biochemical assay demonstrated that all these probionts had the ability in excreting catalase, gelatinase, lipase, oxidase, protease, and anti-quorum sensing. In biofilm inhibition assay, the highest percentage of inhibition of V. harveyi and V. parahaemolyticus were demonstrated by B. pocheonensis strain S-2 (70.36 ± 4.84 %) and L. fusiformis strain A-1 (67.79 ± 4.70 %), respectively. Through microalgae propagation experiment, the inoculation ratio of bacteria and microalgae was fixed to 1:4, and co-culture incubation was monitored for 7 to 8 days. Bacillus sp. strain A-2 and L. fusiformis strain Cl-3 were able to promote the growth of Amphora sp., and Chlorella sp., respectively. Bacillus sp. strain A-2 showed a good correlation after co-cultured with Amphora sp. evidenced by a steep growth of Amphora sp. (8.5 x 105 cells ml−1) in comparison with the control (1.4 x 105 cells ml−1) ) at day 8 of co-culture. The cell density of Chlorella sp. was promoted more than two times due to L. fusiformis strain Cl-3 supplementation (9.9 x 106 cells ml−1) compared with the control (4.2 x 106 cells ml−1), observed at day 7 of co-culture incubation. A preliminary in vivo assay was carried out on Artemia fransiscana nauplii against V. harveyi and V. parahaemolyticus. Probionts were supplied to Artemia as single strain and in multiple strains known as MIX (combinations of all potential probionts) along with respective microalgae. Results revealed that Artemia bioencapsulated with MIX + Amphora sp. showed the highest survival rate (60 ± 4 %) when compared with the control (13 ± 2 %), after challenged with V. harveyi. A significant reduction of vibrios load was observed in Artemia bioencapsulated with MIX + Amphora sp. (7.29 ± 0.02 CFU ml−1) compared with the control (7.31 ± 0.05 CFU ml−1). Meanwhile, for the Artemia challenged with V. parahaemolyticus, a significant survival was observed in Artemia bioencapsulated with L. fusiformis strain A-1 + Amphora sp. (78 ± 2 %); Bacillus sp. strain A-2 + Amphora sp. (78 ± 1 %); L. fusiformis strain Cl-3 + Chlorella sp. (78 ± 2 %) and MIX + Amphora sp. (78 ± 2 %) in comparison with the control (32 ± 1 %). The number of vibrios in Artemia bioencapsulated with B. pocheonensis strain S-2 + Spirulina sp. showed significant reduction (7.16 ± 0.09 CFU ml−1) after challenged with V. parahaemolyticus. In conclusion, the present study proposed that all the potential probionts isolated from microalgae exhibit essential probiotics properties which worth to be studied for application in aquaculture. Two potential probionts (Bacillus sp. strain A-2 and L. fusiformis strain Cl-3) were found to be good promoting bacteria for microalgal growth. Moreover, mixture of all potential probionts is beneficial for Artemia bioencapsulation in conferring protection to Artemia nauplii against pathogenic vibrios in the culture environment.